Mechanisms of inside-out signaling of the high affinity IgG-receptor FcγRI - Brandsma, Arianne M. (Sci Signal, 2018)
Fc receptors (FcR) are an important bridge between the innate and adaptive immune system. Fc gamma receptor I (FcγRI, CD64), the high affinity receptor for immunoglobulin G (IgG), plays roles in inflammation, autoimmune responses, and immunotherapy. Stimulation of myeloid cells with cytokines, such as tumor necrosis factor-α (TNFα) and interferon-γ (IFNγ), increases the binding of FcγRI to immune complexes (ICs), such as antibody opsonized pathogens or tumor cells, through a process known as ‘inside-out’ signaling. Using super-resolution imaging, we found that stimulation of cells with IL-3 also enhanced the clustering of FcγRI both before and after exposure to ICs. The increased clustering was dependent on an intact actin cytoskeleton. We found that chemical inhibition of PP1 activity reduced FcγRI inside-out signaling, although the phosphorylation of FcγRI itself was unaffected. Furthermore, the antibody-dependent cytotoxic activity of human neutrophils towards CD20-expressing tumor cells was increased after stimulation with TNFα and IFNγ. These results suggest that nanoscale reorganization of FcγRI, stimulated by cytokine-induced, inside-out signaling, enhanced FcγRI cellular effector functions.